699 Community mobilisation to establish a community creche to increase child supervision in rural nepal. (1st September 2016) - Pant, Puspa Raj; Ellis, Matthew; Deave, Toity; Mytton, Julie
Abstract : Background: Injuries are among the leading causes of death and hospitalisation of children worldwide; 90% of all injuries are unintentional. In 2010, over 900 children aged 1–4 years died from injuries in Nepal; the extent of non-fatal injuries is unknown. Most of the injuries to younger children occur at home, and associated with lack of supervision. Community mobilisation may be a feasible approach for preventing child injuries in rural Nepal. We describe community mobilisation for developing a community-crèche for 1–3 year old children to increase supervision and promote early childhood development. Methods: We worked with one women's group in Makwanpur and facilitated group discussion; a visit to an established crèche system in Bangladesh; did debriefing and orientation, and community involvement sessions. The women's group formed a committee to develop and manage the crèche; nominating 2 volunteers who were responsible for identifying eligible children and running the crèche. Published minimum standards for early child development centres (ECDC) by the government of Nepal were applied. Results: In February 2015, a crèche was established in Hatiya (Makwanpur) under the ownership of local women's group; and registered with local authority. A qualified ECD trainer trained the volunteers and mothers on stages of childhood development. A total of 17 children aged 1–3 years were enrolled and attended the crèche for 3 to 4 hours daily. Parents observed positive changes in children attending crèche. They also felt their children were in secure place when they were at work. The local municipality provided financial support to the crèche. A local government ECD centre agreed to intake the graduates from the crèche. Conclusion: It is feasible, acceptable and potentially sustainable to establish crèches for young children in Nepal with full ownership of local women's group. There is very high potential for the partnership with local government which can also provide resources.